(untitled) (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: Are the masses feminine? Through a theoretical articulation of political confrontation, we will put points of interconnection between the theory of mass psychology, criticizing its transversality with elements of misogyny and eurocentrism. In a second moment, we will work with the ways in which post-colonial Latin American feminism of the late twentieth century reversed the lebon’s gender polarity as well as its political hierarchies. Keyword: Masses. Feminism. Gender. Postcolonialism.